Sistem Akuntansi Penggajian Pada PT. Bank Sumsel Babel Cabang Pembantu Gelumbang - Irsan; Masnoni; Hilwa Anggraini; Sri Sutandi; Zein Ghozali (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This study aims to determine the payroll accounting system of PT. Bank sumsel Babel Gelumbang.The techniques of data collection are observation,inter views and documentation.Data are analyzed using qualitative descriptive analysis by comparingthe theory withthe facts occur, namely payroll internal control system. The results of analysis show that PT.Bank Sumsel Babel Gelumbang has separated functional duties and responsibilities in each part of the employee payroll process.Network payroll system procedure for employees of PT.Bank Sumsel Babel Gelumbang consists of time at tendance procedure, administrative procedure, payroll procedure, and salary paymentprocedures.Central managementof PT.Bank Sumsel Babel Gelumbang directly handles personneland payroll functions.Payroll system procedure of PT.Bank Sumsel Babel Gelumbang is simple, good, and easy to understand. Employee payroll system of PT. Bank Sumsel Babel Gelumbang has shown its internal control is good enough because there is a separation of duties and responsibilities in its organizational structure, authorizationsystem, good recording procedures, and good practices in carrying out the functions of each organizational unit.